2017
DOI: 10.1038/srep40000
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly discriminate commercial medicinal Pulsatilla chinensis (Bge.) Regel from its adulterants using ITS2 barcoding and specific PCR-RFLP assay

Abstract: Pulsatillae radix is a conventional traditional Chinese medicine (TCM) with common name Baitouweng, and has notable effects on inflammation and dysentery. Pulsatilla chinensis (Bge.) Regel is the only source plant of Baitouweng recorded in Chinese Pharmacopoeia, but its adulteration often occurs in the market that possibly affects medicinal efficacy and safety. We have established an internal transcribed spacer 2 (ITS2) barcode library based on 105 plant samples from 12 Pulsatilla species and 10 common adulter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 51 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…The presence of undeclared species is a common result in studies analysing TMs. In line with the results of chapter 7, recent studies found in the analysis of TMs that up to 98% of the species identified in TMs were not declared on the label [200,[314][315][316].…”
Section: Identification Of Endangered Speciessupporting
confidence: 79%
“…The presence of undeclared species is a common result in studies analysing TMs. In line with the results of chapter 7, recent studies found in the analysis of TMs that up to 98% of the species identified in TMs were not declared on the label [200,[314][315][316].…”
Section: Identification Of Endangered Speciessupporting
confidence: 79%
“…It is also an effective technology for tracing the origin of raw materials and detecting adulterants in herbal medicine sold at markets. Verification of the accuracy and stability of ITS2 as the DNA barcode continues beyond herbal materials [ 33 , 45 , 46 ], and has been applied to Pulsatillae Radix ( Pulsatilla chinensis ) [ 47 ], Rhodiola Crenulatae Radix et Rhizoma ( Rhodiola Crenulatae ) [ 45 ], Notopterygii Rhizoma et Radix ( Notopterygium incisum ) [ 48 ], Menispermi Rhizoma ( Menispermum dauricum ) [ 49 ], and Lonicerae Japonica Flos ( Lonicerae Japonicae ) [ 50 ]. DNA barcoding has also been used to trace the composition of the health food [ 15 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, significant substitution was found in 98% of products of the traditional Chinese medicine (TCM), Baitouweng, which are expected to contain Pulsatilla chinensis (Bge.) Regel (Shi et al, 2017), 26% of single ingredient products purchased from local markets in Iran (Ghorbani et al, 2017), 16% of ginkgo herbal dietary supplements sold as dried and powdered leaves, purchased on-line and in retail stores from the New York area (Little, 2014), 7% of Senna and 50% of Cassia market products in India (Seethapathy et al, 2014), 6% of saw palmetto herbal dietary supplements sold as dry, cut, gelatine capsules and compression tablets, purchased on-line and at retail stores in the New York area (Little and Jeanson, 2013), 25% of black cohosh dietary supplements purchased on-line and at retail stores in the New York area (Baker et al, 2012), 50% of Korean ginseng natural health products capsules, sold as tablets, roots, carved roots, extracts, teas and dried and shredded products, purchased from various commercial sources, including pharmacies and markets in Toronto and New York (Wallace et al, 2012), 35% of herbal tea products purchased from 25 different locations in the New York area (Stoeckle et al, 2011); and in 59% of herbal products sold as capsules, powders and tablets, purchased from the Toronto area or on-line from distributors in the United States (Newmaster et al, 2013). In the wake of these studies and of other recent cases exposing discrepancies between labelling and constituents actually present in the products, serious concerns were raised about the authenticity and quality of herbal products.…”
Section: Dna Barcoding and Metabarcodingmentioning
confidence: 99%